Lênin e a imprensa: o jornal como organizador coletivo da revolução proletária - Seoane, Marcelo Bamonte (2024)
This work aimed to examine the thoughts of the Russian revolutionary Vladimir Lenin about the press. The central problem of the research is based on the need to understand how the newspaper played a role as a collective and political organizer during the Russian revolution and its previous processes. The time frame is based on Lenin’s life, which includes all of his writings on the subject – or that address the issue of the press and journalism. The work aims to understand how the newspaper was a fundamental part of the development of the RSDLP, posthumously PCR (b), showing how it, at the same time as it was a fundamental instrument for bringing together controversies, also assumed the role of organic educator of the Russian working class, at the same time largely illiterate and sparse time, with more than 80% of citizens being peasants and outside urban centers. Journalism represents much more than just the concrete bourgeois needs of a given historical time. Being umbilically linked to immediate reality, it is necessary that this revolutionary ideological conditioning does not lose sight of the need to maintain ties with the objective manifestations of singular phenomena. 1 But journalism itself develops differently given the historical stages set and brings new challenges, especially when it comes to organizing an alternative method to that of the hegemonic press. As we will see later, Lenin will start from many of Marx’s conceptions about journalism, but mainly from observing the press as one of the main means of political and ideological dissemination, using it, above all, as a collective organizer capable of concretely structuring the Russian Social Democratic Labor Party, later, after its split in 1903 and creation of the Union of Soviet Socialist Republics in 1922, the Communist Party of the Soviet Union. For him, it would be impossible to conduct the revolutionary struggle in Russia without a means of dissemination through which the Party could expose its position on concrete situations in the Russian society